Effect of the MOSFET choice on conducted EMI in power converter circuits - Ben Hadj Slama, J.; Tlig, M. (2012 16th IEEE Mediterranean Electrotechnical Conference, 2012)
The phase of virtual prototyping, which is usually based on a whole of numerical simulations of the system, requires today to have thin suitable models. These models must take in account the real behavior of the systems under various physical constraints (thermal, electromagnetic...). Particularly, in this work, we are interested to the study of the effect of the Mosfet transistor choice on the conducted electromagnetic interferences emitted by static converters circuits. The objective of this work is to propose a new design methodology which will permit to assist the power electronics circuit designer in the choice of the active components with the purpose of reducing the electromagnetic disturbances.